Challenges Women with Disability Face in Accessing and Using Maternal Healthcare Services in Ghana: A Qualitative Study - Ganle, John Kuumuori (PLoS One, 2016)
BACKGROUND: While a number of studies have examined the factors affecting accessibility to and utilisation of healthcare services by persons with disability in general, there is little evidence about disabled women's access to maternal health services in low-income countries and few studies consult disabled women themselves to understand their experience of care and the challenges they face in accessing skilled maternal health services. The objective of this paper is to explore the challenges women with disabilities encounter in accessing and using institutional maternal healthcare services in Ghana. METHODS AND FINDINGS: A qualitative study was conducted in 27 rural and urban communities in the Bosomtwe and Central Gonja districts of Ghana with a total of 72 purposively sampled women with different physical, visual, and hearing impairments who were either lactating or pregnant at the time of this research. Semi-structured in-depth interviews were used to gather data. Attride-Stirling’s thematic network framework was used to analyse the data. Findings suggest that although women with disability do want to receive institutional maternal healthcare, their disability often made it difficult for such women to travel to access skilled care, as well as gain access to unfriendly physical health infrastructure. Other related access challenges include: healthcare providers’ insensitivity and lack of knowledge about the maternity care needs of women with disability, negative attitudes of service providers, the perception from able-bodied persons that women with disability should be asexual, and health information that lacks specificity in terms of addressing the special maternity care needs of women with disability. CONCLUSIONS: Maternal healthcare services that are designed to address the needs of able-bodied women might lack the flexibility and responsiveness to meet the special maternity care needs of women with disability. More disability-related cultural competence and patient-centred training for healthcare providers as well as the provision of disability-friendly transport and healthcare facilities and services are needed.